2022
DOI: 10.15311/selcukdentj.1134685
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Fracture Line Type on Repair Resistance in Acrylic Resins Repaired with Graphene Oxide

Abstract: AMAÇ: Farklı kırık hattı şekillerinin ve aralıklarının grafen oksit ile tamir edilmiş polimetil metakrilat (PMMA) rezin örneklerinin kırılma dayanımına olan etkisinin araştırılmasıdır. GEREÇ VE YÖNTEMLER: 65×10×3 mm boyutunda 50 adet standart mum örnek metal bir kalıp kullanılarak hazırlandı. Hazırlanan mum örnekler 5 gruba (n=10) ayrıldı; grup 1: kontrol grubu (kırık hattı oluşturulmayan), grup 2: 0 mm boşluk ve düz yüzeyli kırık hattı, grup 3: 0 mm boşluk ve 45° bevel kırık hattı, grup 4: 2.5 mm boşluk ve dü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Since fractures in dentures are one of the deficiencies of denture base materials, the effect of NP addition at different types and concentrations on the mechanical strength of acrylic was investigated in studies. 4,15,18,19 It has been reported that adding GO NPs at 1% and 2% concentrations improves the properties of the material. 2,10 Therefore, in the study, the effect of adding GO NPs at 1% and 2% concentrations on the fracture strength was examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since fractures in dentures are one of the deficiencies of denture base materials, the effect of NP addition at different types and concentrations on the mechanical strength of acrylic was investigated in studies. 4,15,18,19 It has been reported that adding GO NPs at 1% and 2% concentrations improves the properties of the material. 2,10 Therefore, in the study, the effect of adding GO NPs at 1% and 2% concentrations on the fracture strength was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was reported that the bending strength of the repair surfaces formed in bevel shape was higher than the specimens with straight broken lines, the fracture lines were formed in the form of bevels in this study. 6,15,20 Chemical agents such as MMA, chloroform, acetone, or methylene chloride are used to increase the bond strength between base acrylic and repair acrylic. 16,20 Pereira et al evaluated the bending strength of repaired PMMA specimens by applying different surface treatments (silicon carbide sanding, monomer soaking, and both monomer soaking and sanding).…”
Section: Discussionmentioning
confidence: 99%